Wide-range and sensitive detection of LPS using a transporter@liposome enhanced electrochemical aptasensor - Xinyu Hu; Shukai Song; Ruyu Lin; Weidong Zheng; Haochen Qi; Lin Xu; Jian Zhang (Analytica Chimica Acta, 2026)

Generative imaging sonar forward depth estimation for underwater dense scene reconstruction - Zhengyan Zhang; Yanze Lu; Haochen Hu; Bing Wang; Jinghua Lin; Chih-yung Wen (Ocean Engineering, 2026)

Dabie mountain topography and cross-regional transport regulating nitrate heterogeneity during a severe haze episode in Jiangxi - Haochen Zuo; Mingxuan Xu; Yangfan Jin; Kangjia Gong; Xiang Tu; Yao Wang; Xiaodong Xie; Jiao Wang; Jianlin Hu (Atmospheric Environment, 2026)

Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

High-temperature corrosion mechanism of ferritic stainless steel in steam-hydrogen atmosphere for solid oxide electrolysis cell based on reactive force field method - Enhua Wang; Yajing Zhang; Jingwen Mao; Haochen Dang; Minggao Ouyang; Haoran Hu; Hewu Wang; Yadi Liu; Youpeng Chen; Languang Lu; Dongsheng Ren (Fuel, 2026)

Numerical study on flow characteristics, hydrodynamics, and structural response of an integrated aquaculture platform with WECs and wind turbine - Can Yang; An Hu; Haochen Zhang; Hailong Chen (Ocean Engineering, 2026)

Chebyshev-based dynamic analysis of pre-stressed composite stepped stiffened combined shells - Haochen Hu; Kunpeng Zhu; Rui Zhong; Qingshan Wang; Zhou Huang (Ocean Engineering, 2026)

DFT-enhanced machine learning for accurate PLQY prediction and inverse design of novel MR-TADF materials - Haochen Shi; Yiming Shi; Guangjun Zeng; Haichang Wang; Yumei Hu; Bo Qiao; Zhiqin Liang; Suling Zhao; Man-Chung Tang; Dandan Song (Chemical Engineering Journal, 2025)

Occurrence, distribution characteristics, and potential ecological risks of perfluorinated compounds in major estuaries and adjacent offshore areas in Hainan Island - Yanhong Hu; Yuehua Huang; Haochen Niu; Hongwei Zhao (Marine Environmental Research, 2025)

Seismic response and failure evolution of an irregular slope containing bedding planes and high-position surficial soil layer - Qianqian Feng; Yunsheng Wang; Jianxian He; Xiaolong Hu; Haochen Wu; Dongyu Hu; Shicheng Liu; Tao Tang (Landslides, 2025)

Arbuscular mycorrhizal fungi enhance glyphosate resistance in an invasive weed: Implications for eco-environmental risks - Shanshan Qi; Daiyi Chen; Mengting Yan; Zhiyun Huang; Haochen Yu; Guangqian Ren; Hu'anhe Xiong; Wei Fu; Biying Zhao; Zhicong Dai; Daolin Du; Torsten Thomas (Applied Soil Ecology, 2025)

Advances of Complex Marine Environmental Influences on Underwater Vehicles - Sen Zhao; Haibao Hu; Abdellatif Ouahsine; Haochen Lu; Zhuoyue Li; Zhiming Yuan; Peng Du (Journal of Marine Science and Engineering, 2025)
Underwater vehicles serve as critical assets for global ocean exploration and naval capability enhancement. The marine environment exhibits intricate hydrodynamic phenomena that significantly threaten underwater vehicle navigation safety, particularly in four prevalent complex conditions: surface waves, oceanic currents, stratified fluids, and internal waves. This comprehensive review systematically examines the impacts of these four marine environments on underwater vehicles through critical analysis and synthesis of contemporary advances in theoretical frameworks, experimental methodologies, and numerical simulation approaches. The identified influences are categorized into five primary aspects: hydrodynamic characteristics, dynamic response patterns, load distribution mechanisms, navigation trajectory optimization, and stealth performance. Particular emphasis is placed on internal wave interactions, with rigorous analysis derived from experimental investigations and numerical modeling of internal wave dynamics and their coupling effects with underwater vehicles. In addition, this review points out and analyzes the shortcomings of the current research in various aspects and puts forward some thoughts and suggestions for future research directions that are worth further exploration, including enriching the research objects, upgrading the experimental techniques, and introducing artificial intelligence methods.

Hydrogel-based materials for microbial/enzyme immobilization: Advanced applications in wastewater treatment - Haochen Hu; Wenxin Lu; Shipeng Li; Xingkun Zhou; Chengyuan Zhu; Xingang Wang; Hongliang Dai; Hongya Geng (Chemical Engineering Journal, 2025)

Cascading H2O2 photosynthesis and Fenton reaction for self-sufficient photo-Fenton reactions: A review of recent advances - Maoquan Wu; Xu Guo; Yaodan Cao; Haochen Yu; Zherui Hu; Yang Yang; Tongjie Yao; Jie Wu (Chemical Engineering Journal, 2024)

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

Insights into the complementation potential of the extreme acidophile’s orthologue in replacing Escherichia coli hfq gene—particularly in bacterial resistance to environmental stress - Wenbo Hu; Xingyu Huo; Haochen Bai; Zongling Chen; Jianxin Zhang; Hailin Yang; Shoushuai Feng (World Journal of Microbiology and Biotechnology, 2024)

Thawing of goose meat by simultaneous dual frequency ultrasound for process efficiency: Thawing rate, quality attributes, structural characteristics - Wangbin Shi; Yang Wang; Xingyu Chen; Haochen Hu; Xi Chen; Benjamin Kumah Mintah; Mokhtar Dabbour; Xiangren Meng; Zhaoli Zhang; Ronghai He; Haile Ma (Innovative Food Science & Emerging Technologies, 2024)

Separation performance of graphene oxide nanofiltration membrane intercalated by MWCNTs and α -Fe2O3 nanoparticles - Baowen Liang; Han Hu; Haochen Zhu; Yunhan Yu; Wenzhi He; Guangming Li (Science of The Total Environment, 2024)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

Recognition of airfoil wake structure based on deep learning - Haibao Hu; Xiangbo Du; Haochen Lu; Xiaopeng Chen; Peng Du (Ocean Engineering, 2023)

Physical processes determining the distribution patterns of Nemopilema nomurai in the East China Sea - Song Sun; Haochen Xian; Ziyuan Hu; Xiaoxia Sun; Fang Zhang (Journal of Oceanology and Limnology, 2023)

One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment - Haochen Qi; Lei Xiao; Jayne Wu; Li Lv; Xinyu Hu; Youyi Zhuang; Xiaoru Liu; Wenci Zhao; Fangshuo You; Jian Zhang; Lei Zheng (Food Chemistry, 2023)

Cavitation damage inducing the improvement of jet breaking efficiency during hydrate drilling - Xiaoya Wu; Yiqun Zhang; Chengyu Hui; Haochen Huang; Zhaowen Hu; Gensheng Li; Shouceng Tian (Ocean Engineering, 2023)

Jet-stirred reactor measurements and chemical kinetic study of ammonia with dimethyl ether - Geyuan Yin; Bo Xiao; Hao Zhao; Haochen Zhan; Erjiang Hu; Zuohua Huang (Fuel, 2023)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)